2016
DOI: 10.3389/fnmol.2016.00087
|View full text |Cite
|
Sign up to set email alerts
|

“Soldier's Heart”: A Genetic Basis for Elevated Cardiovascular Disease Risk Associated with Post-traumatic Stress Disorder

Abstract: “Soldier's Heart,” is an American Civil War term linking post-traumatic stress disorder (PTSD) with increased propensity for cardiovascular disease (CVD). We have hypothesized that there might be a quantifiable genetic basis for this linkage. To test this hypothesis we identified a comprehensive set of candidate risk genes for PTSD, and tested whether any were also independent risk genes for CVD. A functional analysis algorithm was used to identify associated signaling networks. We identified 106 PTSD studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…Moreover, that study found overlap in the upstream genes (e.g., TNFα, involved in inflammation) that regulated both PTSD- and cardiovascular-associated genes, as well as overlap in their gene targets (e.g., the NfκB complex, also involved in inflammation). This suggests that the genetic link between PTSD and cardiovascular disorders is likely mediated by common genetic effects on the inflammation and immune systems [32]. Consistent with this, Breen et al [33] found that gene networks critical for immune system functioning were associated with PTSD in gene expression data from two samples of military veterans.…”
Section: Traumatic Stress and Premature Metabolic And Cardiovascular mentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, that study found overlap in the upstream genes (e.g., TNFα, involved in inflammation) that regulated both PTSD- and cardiovascular-associated genes, as well as overlap in their gene targets (e.g., the NfκB complex, also involved in inflammation). This suggests that the genetic link between PTSD and cardiovascular disorders is likely mediated by common genetic effects on the inflammation and immune systems [32]. Consistent with this, Breen et al [33] found that gene networks critical for immune system functioning were associated with PTSD in gene expression data from two samples of military veterans.…”
Section: Traumatic Stress and Premature Metabolic And Cardiovascular mentioning
confidence: 88%
“…Consistent with this, Sumner et al [31] found that genome-wide risk for PTSD was correlated with genome-wide risk for coronary artery disease, with somewhat weaker evidence for shared genetic risk across PTSD and body mass index and insulin levels. Using an alternate methodology, Pollard et al [32] found overlap between the candidate genes previously associated with PTSD and the candidate genes previously associated with cardiovascular disease and type 2 diabetes. Moreover, that study found overlap in the upstream genes (e.g., TNFα, involved in inflammation) that regulated both PTSD- and cardiovascular-associated genes, as well as overlap in their gene targets (e.g., the NfκB complex, also involved in inflammation).…”
Section: Traumatic Stress and Premature Metabolic And Cardiovascular mentioning
confidence: 99%
See 1 more Smart Citation
“…PTSD is frequently associated with the occurrence of comorbid mental disorders such as major depression 1 and other adverse health sequelae including type 2 diabetes and cardiovascular disease. 2,3 Given this high prevalence and impact, PTSD is a serious public health problem. An understanding of the biological mechanisms of risk for PTSD is therefore an important goal of research ultimately aimed at its prevention and mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, overlapping genetic factors may predispose individuals to both PTSD and cardiometabolic disease. Initial evidence for shared genetic effects across PTSD and cardiometabolic traits comes from studies based on twin designs (Vaccarino et al , 2014, Vaccarino et al , 2013) and candidate gene approaches (Pollard et al , 2016). However, to date, research has not examined the genetic overlap of PTSD and cardiometabolic disease using a genome-wide design.…”
mentioning
confidence: 99%